Existential Fulfilment, Religiousness, Values and State of Mental Health: Results of Empirical Research Among Students (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
The target of the conducted research was to find out the relations among existential fulfilment, religiousness, values and health in respondents. The research was performed on the group of one hundred and twenty one students in June 2018. The methods applied in the research: The Existence Scale Questionnaire by Längle, the Scale of the Religious System of Meanings by Krok , the List of Personal Values by Juczyński, the Mental Health Rating Questionnaire GHQ-12 by Goldberg. The results of the author's own research empirically found that self-transcendence is the most significant feature of human existence whereas frustration arising from the strive to achieving sense leads to psychic distress. This means that the will to meaning is a reliable criterion of mental health.
Keywords: Existential fulfilment; religiousness; values; mental health; empirical research